2016
DOI: 10.1111/jeu.12288
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Regulation of mRNA Processing of Polycistronic Transcripts Mediated by DRBD4/PTB2, a Trypanosome Homolog of the Polypyrimidine Tract‐Binding Protein

Abstract: Trypanosomes regulate gene expression mostly by posttranscriptional mechanisms, including control of mRNA turnover and translation efficiency. This regulation is carried out via certain elements located at the 3'-untranslated regions of mRNAs, which are recognized by RNA-binding proteins. In trypanosomes, trans-splicing is of central importance to control mRNA maturation. We have previously shown that TcDRBD4/PTB2, a trypanosome homolog of the human polypyrimidine tract-binding protein splicing regulator, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 74 publications
(86 reference statements)
0
15
0
Order By: Relevance
“…It regulates splicing and prevents transsplicing by binding in the regulatory elements present in the intercistronic region (ICR) of the ubp1 and ubp2 genes. These results indicate that TcDRBD4/PTB2 might act by covering the trans-splicing/polyadenylation signals (De Gaudenzi et al, 2016).…”
Section: Rbps With Rrm Domains In T Cruzimentioning
confidence: 82%
“…It regulates splicing and prevents transsplicing by binding in the regulatory elements present in the intercistronic region (ICR) of the ubp1 and ubp2 genes. These results indicate that TcDRBD4/PTB2 might act by covering the trans-splicing/polyadenylation signals (De Gaudenzi et al, 2016).…”
Section: Rbps With Rrm Domains In T Cruzimentioning
confidence: 82%
“…Increasing evidence suggests that RBPs can act as multifunctional gene expression regulators (Backlund et al, 2020; De Gaudenzi et al, 2016). Here, we built an in-silico method for the large-scale analysis of RBP-driven regulation using correlation as a proxy for mRNA abundance and translational efficiency (TE) of target genes across 80 human heart samples.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, processes like editing and trans -splicing were firstly described in trypanosomatids and later revealed to also occur, in other eukaryotes. However, while in eukaryotes the co-transcriptional RNA processing, surveillance and transport from nucleus to cytoplasm have been widely recognized as regulatory steps in gene expression (Kohler and Hurt, 2007 ), their survey in trypanosomes is very recent (Nazer et al, 2011 , 2012 ; Fadda et al, 2014 ; Antwi et al, 2016 ; De Gaudenzi et al, 2016 ; Kramer et al, 2016 ). Likewise, genome-wide approaches have been used to identify the RNA nature and abundance distribution in the nucleus and the cytoplasm in many eukaryotes (Liao et al, 2010 ; Solnestam et al, 2012 ; Tilgner et al, 2012 ; Zaghlool et al, 2013 ; Bai et al, 2014 ), but such analyses have not yet been reported in trypanosomatids.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the nuclear compartment in the control of the cytoplasmic steady-state transcript levels has been recognized as crucial in eukaryotic gene expression regulation (Kohler and Hurt, 2007 ; Palazzo and Akef, 2012 ) and is also being studied in trypanosomatids (Nazer et al, 2011 , 2012 ; Fadda et al, 2014 ; Antwi et al, 2016 ; De Gaudenzi et al, 2016 ; Kramer et al, 2016 ), for a very recent review see (Clayton, 2016 ). Although specific molecular actors involved in the nucleus-cytoplasmic transport in T. cruzi are being unraveled (Cassola and Frasch, 2009 ; Serpeloni et al, 2011a , b ; Camara Mde et al, 2013 ; Inoue et al, 2014 ), no global analysis of the impact of nuclear compartmentation has been performed yet.…”
Section: Introductionmentioning
confidence: 99%